Penggunaan E-Learning dalam Pembelajaran Bahasa Arab: Fitur Dan Pola Pengajaran - Rachmad Ramadhan; Danial Hilmi; Ahmad Azhari (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
This study aims to describe the use of e-learning in learning Arabic at MAN 1 Konawe Selatan. This research is a qualitative research and the type of research is a descriptive study, because this research does not use numbers in data collection, and only describes the use of e-learning in learning Arabic which focuses on features and teaching patterns. The data were obtained from the results of self-exploration from the researcher as one of the users of e-learning at MAN 1 Konawe Selatan as well as documents and articles related to this discussion. The use of e-learning at MAN 1 Konawe Selatan in learning Arabic is something new, so teachers and students are required to adapt in its use. Teaching patterns were developed to prohibit the four skills: istima' (listening), kalam (speaking), qira'ah (reading) and kitabah (writing). The learning features owned by e-learning at MAN 1 Konawe Selatan include; Video Conferences, Teaching Materials and Computer Based Tests (CBT), so that learning can be done even from a distance (distance learning).